2019
DOI: 10.1093/gerona/glz293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Loads of Torquetenovirus in the European MARK-AGE Study Population

Abstract: Torquetenovirus (TTV) viremia has been associated with increased mortality risk in the elderly population. This work aims to investigate TTV viremia as a potential biomarker of immunosenescence. We compared levels of circulating TTV in 1813 participants of the MARK-AGE project, including human models of delayed (offspring of centenarians [GO]) and premature (Down syndrome [DS]) immunosenescence. The TTV load was positively associated with age, cytomegalovirus (CMV) antibody levels, and the Cu/Zn ratio and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 53 publications
5
18
2
Order By: Relevance
“…In our patient population, older individuals had significantly higher TTV DNA levels. This finding is in line with previous investigations on smaller cohorts and with a large survey for markers of aging (MARK-AGE) [ 29 31 ]. Indeed, in the MARK-AGE study only age and gender showed a significant association with TTV loads but no blood based routine laboratory parameter did.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our patient population, older individuals had significantly higher TTV DNA levels. This finding is in line with previous investigations on smaller cohorts and with a large survey for markers of aging (MARK-AGE) [ 29 31 ]. Indeed, in the MARK-AGE study only age and gender showed a significant association with TTV loads but no blood based routine laboratory parameter did.…”
Section: Discussionsupporting
confidence: 92%
“…Haloschan et al found lower TTV levels for women under the age of 30 when compared to men [ 31 ] but our patient cohort includes only patients older than 30 years of age. Confirming the findings of the MARK-AGE study [ 29 ], TTV DNA levels showed no significant association with the amount of hemoglobin, albumin, CRP or WBC in our cohort.…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis was also confirmed by the observation that the replication of vesicular stomatitis virus is impaired both in primary and tumor senescent cells in comparison to non-senescent cells [54]. Many studies have described a higher prevalence or increased circulating viral load of some viruses, such as cytomegalovirus (CMV) [55] and Torquetenovirus (TTV) [56,57], with aging. The increased grade of inflammation associated with this phenomenon and the association with mortality of TTV and CMV in the elderly highlights the possible involvement of cellular senescence.…”
Section: Cellular Senescence and Response To Virusesmentioning
confidence: 78%
“…TTV infections are acquired soon after birth and result in chronic asymptomatic viremia [24] that can be significantly elevated in immunosuppression [18,25] and immune senescence [20,21,26]. Indeed, in immunocompromised individuals, such as transplant recipients [17], the average copy numbers can be as high as 10 10 /mL of plasma [18].…”
Section: Discussionmentioning
confidence: 99%
“…While local bursts of replication may be common even in healthy individuals, the presence of HHV DNA in sera is a strong indicator of immunosuppression [12][13][14][15][16][17]. TTV infections, on the other hand, result in asymptomatic, lifelong low-level viremia that can be significantly increased in immunosuppression [18,19] and immunosenescence [20,21].…”
Section: Introductionmentioning
confidence: 99%